2011
DOI: 10.1007/s11355-011-0161-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vegetation biomass structure on thermal performance of tropical green roof

Abstract: The passive cooling effect of green roofs in humid, tropical Hong Kong was investigated with reference to three vegetated plots, grass, groundcover herb, and shrub, with contrasting growth form and biomass structure and a bare control plot. Temperature was monitored at 15-min intervals for a year at seven levels: high (H) at 200 cm, middle (M) at 60 cm, low (L) at 20 cm, surface, soil, rockwool (water storage), and roof-tile surface. The findings indicated the crucial roles played by biomass quantity and struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…Previous field and modeling studies in various climatic zones indicate that an individual green roof can reduce roof surface temperature by 15-45 °C, near-surface air temperature by 2-5 °C and building energy consumption by up to 80% [3][4][5][6][7][8][9][10][11][12]. In an extremely compact tropical city such as Hong Kong with severe shortage of ground-level green spaces and intense UHI effects [13,14], green roof could bring significant benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Previous field and modeling studies in various climatic zones indicate that an individual green roof can reduce roof surface temperature by 15-45 °C, near-surface air temperature by 2-5 °C and building energy consumption by up to 80% [3][4][5][6][7][8][9][10][11][12]. In an extremely compact tropical city such as Hong Kong with severe shortage of ground-level green spaces and intense UHI effects [13,14], green roof could bring significant benefits.…”
Section: Introductionmentioning
confidence: 99%
“…9a the evolution of substrate temperature at three different depths (T À2 cm, T À4 cm, T À8 cm), the volumetric water content of the substrate (VWC) and external air temperature (Tout), during a representative week of summer 2012 are shown. The substrate displays a characteristic bell-shaped curve, indicating accumulation of solar heat after sunrise, gradually raising soil temperature to the maximum peak in the early afternoon and then reaching a minimum value at early morning [15].…”
Section: Summer Analysismentioning
confidence: 99%
“…The results of their study revealed that a 100-mm-thick substrate layer of the roof garden can decrease the temperature fluctuations significantly in summer periods. Jim [15] investigated the passive cooling effect of green roofs in humid, tropical Hong Kong with reference to three vegetated plots and a bare control plot. The thermal performance of the three vegetation types demonstrated pronounced variations in air temperatures at different heights, surface temperature, and material temperature at different depths.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their tolerance of extreme temperature and light conditions, warm season turf grasses have been used on green roofs in sub-tropical and tropical climates, although typically supplemental irrigation is provided (Jim 2012;Ju et al 2012;Sutton et al 2012;Chen 2013). Some wetland species have broad habitat tolerances or some ability to withstand short periods of dry conditions.…”
Section: Water Loss Sensitivementioning
confidence: 99%